Rapid autographic method for detection of enzymatic browning inhibitors based on enzyme immobilization - Micheloni, Oscar B.; Farroni, Abel Eduardo; Garcia, Paula; Furlan, Ricardo Luis Eugenio (2018)
This work describes a TLC-coupled bioautographic assay suitable for the separation and detection of apple polyphenol oxidase (PPO) inhibitors from natural extracts. PPO was immobilised in agar containing L-DOPA as substrate and 3-methyl-2-benzothiazolinone hydrazone hydrochloride (MBTH) to enhance colour development. The inhibition was detected as white spots on reddish background. Minimum amount of PPO inhibitors detected was 0.0125 μg of 4-hexylresorcinol, 0.025 μg of ascorbic acid, 0.5 μg of cysteine and 1 μg of kojic acid. The assay was compatible with normal and reverse phase TLC systems and allows detecting compounds that directly had action on the enzyme as well as agents that could convert quinones back to their reduced form. The chromatographic run evidenced the different nature of enzymatic browning inhibitory compounds from garlic and onion extracts. Using natural enzymes will provide a fast and cheap alternative for target specific exploration of natural enzymatic inhibitors.